COMPARATIVE EFFECTS OF DIFFERENT DIETARY CONCENTRATIONS OF β-GALACTO-OLIGOSACCHARIDES ON GROWTH PERFORMANCE, FEED CONVERSION EFFICIENCY AND ORGANS DEVELOPMENT IN BROILERS - M. S. Yousaf; A. Ijaz; K. Ashraf; M. A. Rasheed; A. Hafeez; H. Zaneb; E. Dar; R. Naseer; I. Rabbani; J. Zentek; H. Rehman1 (Journal of Animal and Plant Sciences, 2016)
The study was carried out to compare the effects of three different dietary concentrations of β-galacto-oligosaccharides (β-GOS) on broilers growth performance, feed intake, feed conversion efficiency and organs development. For this study, two hundred, one day old, Hubbard broiler chicks were procured from the commercial hatchery. All the birds were randomly divided into four groups (n = 50), each having five replicas (n = 10). One of the four groups was kept as control (β-GOS-0) and was given corn based basal diet, whereas, birds in other groups were given same basal diets supplemented with β-GOS at 0.1% (β-GOS-1), 0.2% (β-GOS-2) or 0.5% (β-GOS-5) for a period of five weeks. Body weights, feed intake and feed conversion efficiency (FCE) were determined on weekly basis. On day 35, ten birds from each group were slaughtered to collect viscera for organs development. Data were analyzed by one way analysis of variance technique and incase of significant (P < 0.05) results, Tukey's post hoc test was applied. Results demonstrated that growth performance and feed conversion efficiency of β-GOS supplemented birds were improved (P < 0.05) in a dose dependent manner, being the highest body weight (P < 0.05) and improved FCE (P < 0.05) were observed in β-GOS-5 group. Relative weights of liver and pancreas were higher (P < 0.05) in β-GOS-1 group. In conclusion, birds supplemented with 0.5% β-GOS outperformed other supplemented and control groups in growth performance and feed conversion efficiency.
Keywords: β-galacto-oligosaccharides; growth performance; feed conversion efficiency; organs development; broilers